1992
DOI: 10.1002/elan.1140040908
|View full text |Cite
|
Sign up to set email alerts
|

Polarographic and electrochemical studies of some aromatic and heterocyclic nitro compounds, part III: Electroreduction of mono‐ and dinitropyrazoles and ‐imidazoles

Abstract: Institute of General arzd Physicul C b m i s q , Studentski wg 12-16, ABSTRlCTThe reduction of mono-and dinitropyrazoles and of nitroimidazoles f o l l o~~ the general pattern of reduction of aromatic nitro compounds: The nitro group is reduced in a four-electron step to a hydroxylamino group and the protonated form of the hydroxylamino group is-in the lower pH range-further reduced to an amine. This reduction differs from that of nitrobenzenes in participation of a second hydrogen ion probably involved in pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
1
7
0
1
Order By: Relevance
“…Similar stabilization of arylhydroxylamines by dehydration was observed for reductions of some heterocyclic nitro compounds (74,189,190). The incidence of dehydration depends on the mutual position of the nitro group and the ring heteroatom and on the presence or absence of alkylation of this heteroatom.…”
Section: Reactions Interposed Between Two Electron Transferssupporting
confidence: 57%
“…Similar stabilization of arylhydroxylamines by dehydration was observed for reductions of some heterocyclic nitro compounds (74,189,190). The incidence of dehydration depends on the mutual position of the nitro group and the ring heteroatom and on the presence or absence of alkylation of this heteroatom.…”
Section: Reactions Interposed Between Two Electron Transferssupporting
confidence: 57%
“…The electrochemistry of metronidazole has been reported at different electrodes such as mercury [5][6][7][8][9], glassy carbon, DNA-modified glassy carbon and a mercury thin film electrode [10,11]. According to these studies, the reduction of metronidazole in acid medium is pH-dependent and four electrons are involved in the complete reduction to the hydroxylamine derivative.…”
Section: Introductionmentioning
confidence: 97%
“…Zuman and co-workers 5,7,13 showed that the E1/2 for the first reduction step of nitrocompounds is shifted to more negative potentials with increasing pH. This change in the E1/2 values occurs both in aqueous medium and solutions with different percentages of organic solvents.…”
Section: Introductionmentioning
confidence: 97%
“…Under anaerobic conditions or low oxygen pressure, the reduction process is similar to that observed for nitrobenzene 4 . The reduction mechanism for several aromatic and heterocyclic nitrocompounds was presented by Zuman and co-workers [5][6][7][8][9][10][11][12][13] . A total of two electrons and two protons is involved in the formation of the nitroso (R-NO) intermediate, two more electrons and protons result in the hydroxylamine (R-NHOH) [5][6][7][8][9][10][11][12][13][14] In voltammetric studies of nitroimidazole derivatives [15][16][17] , two reduction waves were observed in aqueous acid medium.…”
Section: Introductionmentioning
confidence: 99%